The evaluation of simulation maket in nursing education and the determination of learning style of students - Çelik, Yasemin; Ceylantekin, Yeşim; Kiliç, İbrahim (International Journal of Health Sciences, 2017)
Objective: The aim of this study is to detect the overall evaluation of nursing students toward simulation makets throughout the practice education and to reveal their learning styles in relation to certain individual features. Materials and Methods: The data were collected via questionnaires including students’ evaluation toward simulation makets and “Kolb learning styles inventory.” Participants included 103 male and female nursing students in Turkey. For the analysis, percentage, means, standard deviation, t-test, and ANOVA were utilized. Results: 71% of the students stated that the laboratory was suitable for the skill education but 53.4% uttered the duration of the practice was not enough. Students were found to have different learning styles (28.2% assimilating, 27.2% convergent, 26.2% accommodating, and 18.4% divergent). Conclusion: The results demonstrated that the duration of the laboratory practice and the number of the makets should be increased during the education of students with different learning styles.